Exposure to colistin impairs skin keratinocytes and lateral-line hair cells in zebrafish embryos. (January 2021) - Yen, Hsiu-Ju; Lin, Jia-Rou; Yeh, Ya-Hsin; Horng, Jiun-Lin; Lin, Li-Yih
Abstract: Environmental contamination by antibiotics has become a global issue. Colistin, a cationic antimicrobial polypeptide, has been widely used in human/veterinary medicine, and growth promotion in aquaculture. However, no study has been conducted to test the toxic effects of colistin on aquatic animals. In this study, we examined the effects of colistin on zebrafish embryos. Zebrafish embryos were incubated in different concentrations (0, 0.01, 0.1, 1, 2, 3, and 10 μM) of colistin for 96 h. Colistin increased the mortality rate in a dose-dependent manner (LC50 was 3.0 μM or 3.5 mg L −1 ), but it did not change the hatching rate, heart rate, body length, eye size, or yolk size of embryos. However, colistin impaired keratinocytes and lateral-line hair cells in the skin of embryos. Colistin (at concentrations ≥0.1 μM) decreased the number of FM1-43-labeled hair cells and reduced the mechanotransduction-mediated Ca 2+ influx at hair bundles, suggesting that sublethal concentrations of colistin can impair lateral line function. To investigate the lethal injury, morphological changes were sequentially observed in post-hatched embryos subjected to lethal concentrations of colistin. We found that skin keratinocytes were severely damaged and detached after exposure, leading to hypotonic swelling of the yolk sac, loss of ion contents, cell lysis, and eventual death. This study revealed that acute colistin exposure can impair skin cells and pose a threat to fish survival. Graphical abstract: Image 1 Highlights: Zebrafish embryos were exposed to waterborne colistin (0.01, 0.1, 1, 2, 3, and 10 μM) at 0–96 h post-fertilization. Colistin increased the mortality rate in a dose-dependent manner, 96-h LC50 was approximately 3.0 μM or 3.5 mg L −1 . Sublethal concentrations (o.1 and 1 μM) of colistin impaired lateral-line hair cells and mechanotransduction. Lethal concentrations of colistin severely damaged skin keratinocytes, leading to osmotic lysis of embryonic cells. Exposure to water-borne colistin (0.1 μM) might pose a threat to fish survival.